Influence of sex and task difficulty on switching attention (2017)
In this paper, we study complex or executive attention based on sex and difficulty of switching attention task. An experimental study was carried out using a mixed complex 2 × 4 design in which 48 students participated performing the Complex Attention task of the Spanish version of PSSCogRehab 2012 software. Data analysis was performed using a factorial variance analysis for mixed complex designs and the Mann-Whitney U-statistic. The results showed that there are no significant differences between the performance of males and females in terms of success, however, males tend to be faster when the switching attention task is easy; the gap between the sexes ceases to be significant as the level of complexity of the task increases. It was found that the difficulty of the task significantly influences the process of attentional change since as the level of complexity increases, the successes decrease and the response time increases in both sexes. The global change costs of men and women were estimated at different levels of difficulty, however, no significant differences were found between sexes. These results suggest similarities rather than differences between the sexes, at least in a cognitive process, which has social, educational and even clinical implications related to the evaluation of executive attention and the treatment of attentional disorders. © 2017 Universitat de Barcelona